Prarancangan Pabrik Asetaldehida dengan Proses Dehidrogenasi Etanol Kapasitas 30.000 Ton/Tahun - Ainiyah, Oktaviana Lupita; , Ir.Herry Purnama, M.T., Ph.D; , Ir. Haryanto AR., M.S (2016)
Acetaldehyde in Indonesia still needs to rely on imports from abroad. For that is the establishment of acetaldehyde plant with a capacity of 30.000 ton/year is very important to meet the needs of acetaldehyde in Indonesia. Raw material for making acetaldehyde is ethanol reacted dehydrogenation process using the fixed bed multitube reactor at a temperatur of 260-290oC and a pressure of 1,25 atm with solid catalyst Cr2Cu2O5. This reaction takes place in endothermic and irreversible. Conversion of reaction is 50% and yield 85%. The manufacturer of acetaldehyde plant will be established in Gresik, East Java by area 60.000 m2. Total raw material requirement ethanol is 7920,9102 kg/hr, total product produced is 3750 kg/hr, total water needs for all units is 105,8817 m3/hr, total electricity needs is 194,0699 kW and total fuel needs is 99,7345 L/hr. Based on economic analysis, the manufacturer of acetaldehyde plant requires fixed capital and working capital of Rp 537.996.201.110,92 and Rp 425.706.083.282,58, other than that obtained return of investment before taxes of 38,91%, after taxes of 27,24%, break even point 46,68%, shut down point 26,28%, pay out time before taxes of 2,04 year, after taxes of 2,69 year, and discounted cash flow 24,2%. Based on the calculation of the economic analysis, it can be concluded that this manufacturer of acetaldehyde plant is reasonable to establish.